Impacts of family variables to student’s vocational orientation - Ngo Anh Tuan; Le Thi Tuyet Mai; Than Do Dieu Huong (Journal of Technical Education Science, 2014)
Career choice has implications for national development. In every society, the quality of workers as well as their job satisfaction contributes directly or indirectly to economic stability and social affairs of the nation. Career orientation is effected by many variables, in which family plays a very important role. Attitudes about work and careers of young people are formed by interactions with the family. Family background provides the basis from which their career plans and decision making evolve. In Vietnam Society, students usually grow up under the support of their family, so family is not only the first educational environment but also the first vocational school for the youth, and specially the first vocational teachers - their parents. However, within each family, the level of involvement can vary, offering both positive and negative influences. Generally, it is believed that the primary motive behind the pursuit of various occupations is the fundamental human need to satisfy needs. Human need is affected mostly by family background. Occupation and family background form a way of life. They shape one’s characteristic, determine one’s social status, style of life…. These implies that the choice of occupation and family education has a closed connection and after that one’s entire way of life.This research studies deeply into the influence of family factors on career choice. Specifically, it picks on the influence of family variables (parental background, labor value viewpoints, self - awareness) on the career choice of more than 500 students from Nong Lam University.